2015
DOI: 10.3390/w7052349
|View full text |Cite
|
Sign up to set email alerts
|

China’s Policy on Dams at the Crossroads: Removal or Further Construction?

Abstract: During the past century, the number and scale of reservoirs worldwide has grown substantially to meet the demand for water and hydropower arising from increased population, industrialization, and urbanization. This is particularly the case in China, where reservoir construction increased rapidly after the Chinese economic reform and the introduction of open-door policies. On average, 4.4 large reservoirs with a capacity greater than 0.1 km 3 were constructed per annum during the 1970s-1990s. This average reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…This is consistent with the results of R 2 values (Table 3), which indicated that the correlation of the GDP data with reservoir capacity was higher than that with the number of large dams. In addition, there has been a boom in dam construction since Chinese economic system reform and the introduction of open-door policies in the 1970s [38,39]. According to the study of Miao et al, on average 4.4 reservoirs with a reservoir capacity larger than 0.1 km 3 were constructed per annum during the 1970s-1990s, and the pace of construction accelerated after 2000, with an average of 11.8 such reservoirs constructed per annum in the 2000s [38].…”
Section: Relationship Of Large Dams With Gdpmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the results of R 2 values (Table 3), which indicated that the correlation of the GDP data with reservoir capacity was higher than that with the number of large dams. In addition, there has been a boom in dam construction since Chinese economic system reform and the introduction of open-door policies in the 1970s [38,39]. According to the study of Miao et al, on average 4.4 reservoirs with a reservoir capacity larger than 0.1 km 3 were constructed per annum during the 1970s-1990s, and the pace of construction accelerated after 2000, with an average of 11.8 such reservoirs constructed per annum in the 2000s [38].…”
Section: Relationship Of Large Dams With Gdpmentioning
confidence: 99%
“…In addition, there has been a boom in dam construction since Chinese economic system reform and the introduction of open-door policies in the 1970s [38,39]. According to the study of Miao et al, on average 4.4 reservoirs with a reservoir capacity larger than 0.1 km 3 were constructed per annum during the 1970s-1990s, and the pace of construction accelerated after 2000, with an average of 11.8 such reservoirs constructed per annum in the 2000s [38]. The increasing rate of the reservoir capacity was 22.42 km 3 per annum after 2000, which was nearly twice as much as that before 2000 (i.e., with a rate of 12.44 km 3 per annum) (see Figure 4b).…”
Section: Relationship Of Large Dams With Gdpmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the world went from having 9,056 large dams in 1960 to accounting for more than 32,500 in 2010 (World Bank, 2013). However, other sources assert that during the 20th century more than 47,000 large dams and 800,000 small dams were built around the planet (Richter and Thomas, 2007;WCD, 2000), highlighting Asia as the continent with the most dams (World Bank, 2013), especially due to China's hydroelectric development (Miao et al, 2015).…”
Section: Dams Around the Worldmentioning
confidence: 99%
“…In the past several decades, the river's streamflow has changed greatly due to climate change and intensive human activities (Dai, Chu, Du, Stive, & Hong, ; Zhao et al, ). The Yangtze River was blocked by the Three Gorges Dam (TGD) in 2003, which had dramatic impacts on the downstream hydrologic regimes and ecological processes (Miao, Borthwick, Liu, & Liu, ; Yang et al, ). On the basis of dam construction, Gao et al (), Wang, Rhoads, and Wang (), and Wang et al () used IHA and ecoflow metrics to evaluate hydrologic alteration in the upper Yangtze River; Duan, Guo, Wang, and Liu () and Yu, Wang, Wang, Hou, and Qian () investigated streamflow changes in the Yangtze River, except the middle reach, using IHA and range of variability approach (RVA); Jiang, Ban, Wang, and Cai () assessed the hydrologic alteration along the whole reaches of the Yangtze River below the TGD with IHA and RVA.…”
Section: Introductionmentioning
confidence: 99%